Evalution of Parangipattai Rasayanam Internal and Lasunathy Thylam External Drugs Choices for Preclinical and Clinical Studies on the Kumbavaatham Periarthritis Shoulder - Vithyapathi Velmurugan, Dr (International Journal of Pharmaceutical & Biological Archive, 2014)
Evalution of Parangipattai Rasayanam Internal and Lasunathy Thylam External Drugs Choices for Preclinical and Clinical Studies on the Kumbavaatham Periarthritis Shoulder